Surgical Treatment Options in Thumb Carpometacarpal Osteoarthritis: A Recent Literature Overview Searching for Practice Pattern with Special Focus on Total Joint Replacement - Schmidt, Ingo (Current Rheumatology Reviews, 2015)
Thumb carpometacarpal joint osteoarthritis is the most common site of non-rheumatic degenerative lesion in the hand, and there are special features in rheumatic patients. None of various surgical treatment options can be declared as
Keywords: resection arthroplasty